Implementasi Kebijakan Pengelolaan Dana Desa Di Desa Dulamayo Selatan Kecamatan Telaga Kabupaten Gorontalo - Mimin S Alisaha; Arifin Tahir; Irawaty Igirisa (Jambura Journal of Administration and Public Service, 2022)
ABSTRACT This study aims to identify and describe: (1) How to implement Village Fund management policies in Dulamayo Selatan Village, Telaga District, Gorontalo Regency, and (2) Factors that determine the success of implementing Village Fund management policies in Dulamayo Selatan Village, Telaga District, Gorontalo Regency. The approach used is qualitative with descriptive research type. Collecting data using interviews, observation and documentation. Data analysis used the Miles and Huberman model. The results of the study show: (1) The implementation of village fund policy management in Dulamayo Selatan Village is not yet fully optimal even though at the planning, implementation, reporting and accountability stages and the supervision process has followed Permendagri No. 20 of 2018 concerning village financial management. However, there are still some problems such as low community participation in socialization and discussion meetings regarding the management of village funds, the development implementation process is still hampered, the reporting process such as physical documents before and after work that should be made by the TPK is still assisted by village officials and monitoring process that is not too intense; (2) The factors that determine the success of implementing the Village Fund management policy in Dulamayo Selatan Village are not fully supported. This is due to the lack of community participation in the communication process, inadequate human resources and facility resources, then the inconsistency of commitment from the attitude of the activity implementers and, in terms of bureaucratic structure, the activity implementing team has not been fully able to carry out its main tasks and functions.